2014
DOI: 10.1371/journal.pone.0110774
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cold Exposure on Leukocytes, Hormones and Cytokines during Acute Exercise in Humans

Abstract: The purpose of the study was to examine the effects of exercise on total leukocyte count and subsets, as well as hormone and cytokine responses in a thermoneutral and cold environment, with and without an individualized pre-cooling protocol inducing low-intensity shivering. Nine healthy young men participated in six experimental trials wearing shorts and t-shirts. Participants exercised for 60 min on a treadmill at low (LOW: 50% of peak VO2) and moderate (MOD: 70% VO2peak) exercise intensities in a climatic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
4
21
0
4
Order By: Relevance
“…In another study, researchers found that trigeminal nerve stimulation using cold sprays and fan on the face was associated with a reduction in heart rate during exercise [14]. Although these mechanisms should be further investigated by measuring skin blood flow and stroke volume, our current results suggest that even mild body cooling reduces heart rate during exercise, similar to previously published data [3][4][5][6].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In another study, researchers found that trigeminal nerve stimulation using cold sprays and fan on the face was associated with a reduction in heart rate during exercise [14]. Although these mechanisms should be further investigated by measuring skin blood flow and stroke volume, our current results suggest that even mild body cooling reduces heart rate during exercise, similar to previously published data [3][4][5][6].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies examining the effects of exposure to cold on physiological parameters have typically decreased ambient temperature as a method for exposure to cold [3][4][5][6]. In the present study, the ambient temperature and relative humidity were the same in the mild body cooling and control trials.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Quando a integridade do corpo é alterada há a ativação de vias de sinalização neuroendócrinas e os exercícios físicos atuam tanto como estressores como modificadores da resposta sistêmica. Utilizada como um confiável modelo de estresse físico, a atividade física promove modificações nas concentrações séricas de hormônios do estresse como catecolaminas (epinefrina e norepinfrina), hormônio do crescimento (GH), cortisol e dos hormônios sexuais (testosterona e estrógeno) (GAGNON et al, 2014;KRÜGER et al, 2011;LANCASTER et al, 2004;PEDERSEN;HOFFMAN-GOETZ, 2000).…”
Section: A Atividade Física Modulando Os Sistemas Endócrino E Imuneunclassified
“…O aumento na produção de testosterona durante o exercício físico pode modular a atividade de macrófagos e linfócitos, que possuem receptores para hormônios sexuais, podendo aumentar a suscetibilidade a infecções em atletas profissionais (GAGNON et al, 2014;HEJAZI;HOSSEINI, 2012;PEDERSEN;HOFFMAN-GOETZ, 2000 , v. 9, n. 1, p. 175-186, jan./abr. 2016 -ISSN 1983-1870 -e-ISSN 2176-9206 …”
Section: A Atividade Física Modulando Os Sistemas Endócrino E Imuneunclassified